2022
DOI: 10.1111/jcpt.13722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body weight on bleeding events of aspirin in ischemic stroke or transient ischemic attack patients

Abstract: What is known and objectives Bleeding is the most common adverse reaction to aspirin and can lead to drug discontinuation or even be life‐threatening in the secondary prevention of stroke or transient ischemic attack. The aim of this study was to evaluate risk factors for bleeding adverse reaction of aspirin in ischemic stroke or transient ischemic attack. Methods This retrospective analysis included patients treated with aspirin (100 mg) as a secondary prevention for ischemic stroke or transient ischemic atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
(40 reference statements)
0
10
1
Order By: Relevance
“…The main difference between the study results of Wang et al 1 and those obtained in our study consists in the proportion of patients with bleeding (10.0% vs. 2.7%) due to incomplete documentation of non-severe bleeding events in German general practices. While the associations observed in our study were not significant due to the small absolute numbers of bleeding events, the trend observed fully confirms the findings of Wang et al 1 Further studies are needed to confirm these findings and gain a better understanding of the reasons for the increased risk of bleeding in underweight stroke and TIA patients treated with aspirin.…”
contrasting
confidence: 94%
See 1 more Smart Citation
“…The main difference between the study results of Wang et al 1 and those obtained in our study consists in the proportion of patients with bleeding (10.0% vs. 2.7%) due to incomplete documentation of non-severe bleeding events in German general practices. While the associations observed in our study were not significant due to the small absolute numbers of bleeding events, the trend observed fully confirms the findings of Wang et al 1 Further studies are needed to confirm these findings and gain a better understanding of the reasons for the increased risk of bleeding in underweight stroke and TIA patients treated with aspirin.…”
contrasting
confidence: 94%
“…A body weight of below 60 kg was a risk factor for overall bleeding and gastrointestinal bleeding events. 1 We conducted a very similar study in Germany based on data from the IQVIA Disease Analyzer database which contains basic demographic variables, diagnoses, prescriptions, and lab values. 2 A total of 4482 patients with a first prescription of aspirin 100 mg following stroke or TIA in 2010-2020 were included.…”
mentioning
confidence: 99%
“… 4 , 29 When aspirin is administered to patients with a low muscle mass, bleeding events are more likely to occur because of a relatively high level of salicylic acid in systemic circulation and a decrease in prostacyclin production in endothelial cells. In addition to pharmacodynamic studies, observational studies of clinical outcomes have explored the correlation between body weight and aspirin-induced bleeding, 12 and it was reported that patients with lower body weight (≤60 kg) were at increased bleeding risk with 100 mg aspirin. However, few studies have been reported on the correlation between body composition and aspirin-induced bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may influence the pharmacodynamics and pharmacokinetics of aspirin and is associated with impaired aspirin responsiveness. 9 , 10 Previous trials 11 , 12 have suggested that the risk of aspirin-induced bleeding is related to the body weight, and participants with a lower body weight seem to be at a high risk of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“… 38 , 39 These results suggest an association between body weight and aspirin dosage: low-dose aspirin (75–100 mg/d) is only effective in preventing vascular events in patients weighing less than 70 kg, 40 and patients weighing < 60 kg are more likely to experience bleeding events. 41 , 42 In addition, aspirin-mediated reductions in the long-term risk of CRC are also weight dependent, and it has been reported that aspirin 75–100 mg/d reduces the risk of CRC in participants weighing less than 70 kg but not in people weighing 70 kg or more. 40 Therefore, a one-dose-for-all approach to aspirin use in elderly individuals is unlikely to be optimal and an individualized therapeutic strategy is warranted.…”
Section: Discussionmentioning
confidence: 99%